2010
DOI: 10.1007/s11060-010-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 promotion of glioblastoma cell invasion and angiogenesis in U251 and T98G cell lines

Abstract: Interleukin-6 (IL-6) is a growth and survival factor in human glioblastoma cells and plays an important role in malignant progression. However, its role in glioblastoma invasion is still unknown. This study shows how IL-6 promotes cell invasion and migration in U251 and T98G glioblastoma cell lines. The underlying mechanism includes both protease-dependent and -independent manners. Stimulation with IL-6 increased MMP9 expression in the two cell lines but had no influence on MMP2 expression. Fascin-1 is a cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 44 publications
4
113
0
Order By: Relevance
“…Fascin levels can be abnormally high in many cancers (18 -20), and this work shows that IL-6 or OSM treatment can further increase these levels to promote cell migration (21). It is also possible that other factors, such as ␤-catenin and cAMPresponse element-binding protein, contribute to the expression of fascin in cancer cells (30 -32).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Fascin levels can be abnormally high in many cancers (18 -20), and this work shows that IL-6 or OSM treatment can further increase these levels to promote cell migration (21). It is also possible that other factors, such as ␤-catenin and cAMPresponse element-binding protein, contribute to the expression of fascin in cancer cells (30 -32).…”
Section: Discussionmentioning
confidence: 87%
“…However, it is not known how fascin expression is elevated in metastatic tumor cells. It has been reported that IL-6 increases the expression of fascin in glioblastoma cells to promote cell invasion (21). This observation suggests a correlation between STAT3 activation and an increase in fascin expression.…”
mentioning
confidence: 84%
“…Furthermore, we found IL-6 and ICAM1, which are upregulated only in high-risk tumors, as the key mediators of chemosensitivity. In good correlation, IL-6 and ICAM1 were found associated with invasion, angiogenesis, tumor growth, chemoresistance, and prognosis in many cancers (29)(30)(31)(32). .…”
Section: Discussionmentioning
confidence: 89%
“…1E). We also investigated the expression of several cytokines, which are previously reported to promote invasion or angiogenesis in glioma (36,37). The expression of IL-2, IL-6, and IL-10 were upregulated in U87R cells compared with U87 cells (Fig.…”
Section: Establishment Of Temozolomide-resistant U87 Gbm Cell Linementioning
confidence: 97%